(untitled) (Eurasian Journal of Philology Science and Education, 2022)
The article deals with the traditions and ethnodeformations associated with the funeral, which are found in prose works of Kazakh literature. We often use the phrase “torkaly toi, toprakty olim” (solemn celebration a sorrowful death, when all burial ceremonies are performed by beautifying the dead and all close people of the deceased mourn for his/her passing) in the sense of joy and sadness. We know that each nation has its own traditions, superstitions, rituals and customs. Although any of these rituals and customs are common to the Turkic peoples, it can be noted that each nation has its own distinctive features. Over the years, both new and old traditions have been deformed and changed due to time. The initial forms of traditions and the ways they have been ethnodeformed can be seen from scientific research, from the conditions of performing rituals and traditions in fiction. To such funeral customs as farewell to the deceased, the ablution of the deceased, the preservation and protection of the corpse, the participation in the washing of the corpse, the praying for the deceased, the burial, there’re also such rituals as conveying the tragic news of the deceased to his close relatives, mourning for the deceased, expressing condolences to the family of the deceased, as well as giving memorial dinners after seven, forty, one hundred days and a year in the memory of the dead person. The article provides a definitive analysis of the significance and national cognitive features of such rituals. In particular, the relevance of the article is determined by making systematic comparisons through Mukhtar Auezov’s novel-epopee “Abai’s way”, which describes the national existence of the Kazakh people and national traditions in connection with the events.